"A tight, mesmerizing chain of echoes": the pantoum in Irish poetry. Issue 1 (2nd January 2020) - Keating, Kenneth
ABSTRACT: This article maps out the history of the pantoum form, from its origins in Austronesian culture as a pantun, to its emergence in modern Irish poetry. It is contended here that the pantoum represents the manifestation of cultural appropriation and distortion by the colonial oppressor, specifically that of the European colonisers of Austronesia. Detailed evidence for this argument is provided, drawing out the Francophone and Anglophone manipulations of the form as it developed in the Nineteenth and Twentieth Centuries. This essay proceeds to interrogate the use of the form by modern Irish poets to suggest that, while the continued use of this form risks perpetuating colonial oppression, Irish poets attentive to the history of the form foreground transnational cultural hybridity in an effort to not divest the form of its rich history and its importance in Austronesian culture. This conclusion is reached through close readings of texts by Anthony Cronin, Paul Muldoon, Nick Laird, Caitríona O'Reilly, Eleanor Hooker, and Justin Quinn.